Challenges, barriers, and obstacles facing virtual teams: a conceptual study - Alkoud, Saleh; Zainudin, Dolhadi; Mhd. Sarif, Suhaimi (Human Resource Management Academic Research Society, 2023)
Organizations and companies tend to employ virtual teams significantly. The problem of the study stems from the fact that there is a great contradiction between the increasing use of virtual teams in the field of business and their failure rate. Where the importance of virtual teams and their employment in the field of business is increasing greatly in recent years, especially with the great technological progress in information and communication technology and after the spread of Covid 19, and on the opposite side, previous studies indicate a large failure rate in virtual teams, which calls for more studies on the challenges that we experience the success of virtual teams. The importance of this study stems from filling the gap in previous studies that did not adequately cover this aspect. The current study concluded that there are three main groups of challenges facing virtual teams, which are diversity challenges (culture diversity, languages diversity, time zones diversity, and geographical diversity); technical challenges (first-generation technologies, second-generation technologies, and third-generation technologies); and social challenges (conflict, communication, trust, and cohesion).